Anesthesia Complications as a Childbirth Patient Safety Indicator. Issue 3 (September 2015) - El Haj Ibrahim, S.; Fridman, M.; Korst, L.M.; Gregory, K.D.
<x xml:space="preserve">Abstract</x> (Anesth Analg. 2014;119(4):911–917)